One-Way Fluid Structure Interaction of a Go-Kart Spoiler Using CFD Analysis - Mohammad AL-Rawi; Abderrahmane Oumssount (Proceedings, 2020)
The spoiler on a go-kart is required to prevent the vehicle becoming airborne at speeds of 80 km/h or more. An optimal spoiler design balances this safety aspect with speed and fuel economy. This paper reports the results of a project to improve the aerodynamic aspects of a go-kart spoiler design using CFD Analysis. We investigated the design of a rear spoiler with three proposed angles (θ1 = 9.5°, θ2 = 19.5°, θ3 = 29.5°). The drag force produced by each of the three designs is compared. Different computational results are discussed such as the air flow velocity, pressure and the applied forces in terms of CFD analysis using one-way fluid structure interaction (one-way FSI) to determine the spoiler stress, strain and drag coefficient. The findings of this paper have implications for the leisure and tourism industries, and may be applicable to other recreational vehicles’ spoilers.